Neutron production in black hole coronae - Vieyro, Florencia Laura (2013)
We study the injection of neutrons in the corona of Galactic black holes. Since neutrons are not coupled to the magnetic field, a fraction may escape and penetrate the base of the jet, later decaying to create protons. This is a possible mechanism to load Poynting-dominated outflows with protons. Additionally, since neutrons have a mean lifetime of $sim 880$ s, the most energetic neutrons can escape the binary system and inject a considerably amount of energy far from the source. We also investigate the fate of those neutrons and their impact on the interstellar medium.